DNA barcoding of museum-vouchered samples collected from fish markets reveals an unexpected diversity of consumed gastropods in Vietnam - Davin H.E. Setiamarga; Moe Shimizu; Satoko Nakashima; Chihiro Osaki; Kazuki Hirota; Lukytawati Anggraeni; Do Van Tu; Takenori Sasaki (Future Foods, 2025)
Despite the rich diversity of marine gastropods, limited taxonomic investigations on edible species raise concerns regarding fisheries management and food safety in Vietnam. In this study, we employed iterative taxonomy by combining morphological identification and DNA barcoding using the COI, 12S-rRNA, 18S-rRNA, 28S-rRNA, and histone H3 gene markers, to confirm the taxonomy of 126 marine gastropod museum specimens collected from various fish markets in Vietnam. Morphological identification assigned 113 of the 126 specimens to 53 species. Sequences were obtained for all samples, although not all genes were successfully sequenced for every specimen. When all gene markers were used, 58 % in 2023 and 79 % in 2025 of the 113 samples were identified at the species level (excluding the morphologically unidentified individuals), compared to only 51 % in 2023 and 62 % in 2025 when only COI was used. The higher match rates in 2025 likely reflect ongoing improvements in public reference databases. Phylogenetic and genetic distance analyses supported these results, revealing monophyletic species and genera. This study revealed that >50 species are part of local diets, emphasizing the importance of fundamental biodiversity studies, including alpha taxonomic surveys, for managing marine gastropod fisheries and highlighting marine gastropods’ potential as novel food resources. By utilizing vouchered museum specimens, this study also contributes to developing a reliable reference database for identification and monitoring edible marine gastropods in Vietnam and Southeast Asia.